The teaching of physics in engineering curricula - Duarte, Julio Enrique; Caballero, Faustino Reyes; Morales, Flavio Humberto Fernandez (Universidad Pedagógica y Tecnológica de Colombia, 2013)
In this paper we present our reflections on the teaching of physics in engineering curricula. In conclusion, think that even with the limitations of space and time, a micro-design of the courses Basic Physics to be included in the curricula of Engineering were presented, considering aspects of motivation, content and programming.